Afterword: Toward decolonizing anthropology's public spaces. (17th September 2020) - ATHENA ULYSSE, GINA; GUEST, KENNETH J.
Abstract : A child observes a moment of silence for Mike Brown on the third anniversary of his death. The memorial photos are of deceased Ferguson activists Darren Seals and Edward Crawford. Canfield Drive, Ferguson, August 9, 2017. (Carolina Hidalgo / St. Louis Public Radio)